Fostering ecological awareness and pro-environmental intentions through gamification in high school students - Talavera-Mendoza, Fabiola; Cahuana Suni, Nérida Reyna; Cayani Caceres, Karina Sandra (Frontiers in Education, 2025)
This study examines the relationship between the perception of a gamified experience and the ecological awareness of high school students, using the serious game ABCCI (Aprendizaje Basado en la Creatividad Científica; Learning Based on Scientific Creativity). A quantitative correlational design was applied with 197 students who interacted with the game and subsequently completed two questionnaires to assess both their perception of the gamified experience and their ecological awareness. The results revealed a strong and significant positive correlation between a positive perception of the gamified experience and higher self-reported ecological awareness (r = 0.725, p < 0.001). These findings indicate that gamified elements can effectively enhance student engagement and environmental consciousness in educational contexts. However, as the evidence is correlational and based on self-reported data, it does not allow conclusions about long-term behavioral changes beyond the classroom. The study provides empirical support for the association between gamified learning and ecological awareness, offering valuable implications for the design of educational environments that aim to promote pro-environmental attitudes among students.